Glucocorticoid receptor and serum‐ and glucocorticoid‐induced kinase‐1 in esophageal adenocarcinoma and adjacent Barrett's esophagus. Issue 6 (15th March 2020) - Gokon, Yusuke; Fujishima, Fumiyoshi; Taniyama, Yusuke; Ishida, Hirotaka; Yamagata, Taku; Sawai, Takashi; Uzuki, Miwa; Ichikawa, Hirofumi; Itakura, Yuko; Takahashi, Kazutomi; Yajima, Nobuhisa; Hagiwara, Motohisa; et al.
Abstract : Barrett's esophagus (BE) is a consequence of gastroesophageal reflux disease and is predisposed to esophageal adenocarcinoma (EAC). EAC is an exemplar model of inflammation‐associated cancer. Glucocorticoids suppress inflammation through glucocorticoid receptor (GR) and serum‐ and glucocorticoid‐induced kinase‐1 (Sgk1) expressions. Therefore, we immunolocalized GR and Sgk1 in EAC and the adjacent BE tissues and studied their association with clinical disease course in 87 patients with EAC who underwent surgical resection (N = 58) or endoscopic submucosal dissection (N = 29). Low GR and Sgk1 expressions in adjacent BE tissues were associated with adverse clinical outcomes ( P = 0.0008 and 0.034, respectively). Patients with low Sgk1 expression in EAC cells exhibited worse overall survival ( P = 0.0018). In multivariate Cox regression analysis, low GR expression in the adjacent nonmalignant BE tissues was significantly associated with worse overall survival ( P = 0.023). The present study indicated that evaluation of GR and Sgk1 expressions in both the EAC cells and adjacent nonmalignant BE tissues could help to predict clinical outcomes following endoscopic and surgical treatments. In particular, the GR status in BE tissues adjacent to EAC was an independent prognostic factor.